Psychology and miscegenation: an historical and psychoeducational approach - Orellana Manrique, Oswaldo (2005)
The present investigation was realized in three environments of socialization: coast, saw and jungle, with the aim to establish the differences that exist in certain psychological characteristics in school young men who are autoqualified with certain stereotype. For the historical evaluation it has taken in one counts the production of knowledges of the social sciences and for the psychological evaluation a scale of attitudes was doing the life that measures resentment. The product of the investigation involves topics of identity and of social integration, from a historical and psychological perspective very important, so much from the practical like theoretical point of view, since it turns into a valuable information for the education and the psychology, into the comprehension of different human groups that coexist in the Peru. As the topic of miscegenation it does not have precedents for his psychological evaluation, and given the historical violent characteristics in his development, the category has been selected resentment as a distinguishable feature, formulating two aspects to investigating, the historical and different empirical one. One thinks that significant differences exist in the students socialized in all three investigated regions, like that we have that the students of the coast obtain minor score in the scale for the life, whereas in the saw a score prevails over the median, meaning absence of resentment and a socialization with minor discrimination. In the jungle the results indicate that the attitude was doing the life it is more homogeneous, that is to say that they are not scores objected since it is given in the coast and saw.